Investigation of Two-Wheeled Road Traffic Accidents using Explicit FE Techniques. - McLundie, W. M. (Cranfield University, 2007)
With the increase of road traffic accidents increasing due to motorised traffic in the developing world growing alongside the more traditional bicycles and light motorcycles there is good reason to re-examine the two-wheeler case. In addition, if you include the large congestion charge scheme now underway in London and similar projects being considered in other cities globally, there is an even stronger case. These schemes encourage commuters to get back onto two wheels but with a potential increase in road traffic accidents. The development of Explicit Finite Element Analysis (FEA) over the last 15 years, and large improvements in solver times has made examination of complex impact events achievable. As an extension of this knowledge it is now beginning to be feasible to consider the complex case of injury to vulnerable road users (VRU's). This thesis describes why two-wheeler accidents are increasingly relevant, and the details of which injuries are most common in each particular case. From physical testing, bicycle models for adult and child cases were created and the most relevant car to cyclist accident scenarios re-constructed. Existing humanoid models and vehicle models were adapted to understand biomechanical effects in the collision. The results show that although there is great variation due to this complex event in terms of biomechanical and frictional effects and therefore the resulting kinematics, as a mathematical method of investigating future protection devices it should be possible to gain a greater understanding of their effects in the real world. To this end a final section detailing the development of active and passive technologies (including structural optimisation techniques) has been included.